(untitled) (Marketing Journal, 2025)
This article analyzes the effectiveness of digital marketing strategies in enhancing the competitiveness of small business entities. The study examines the impact of SEO (search engine optimization), social media marketing (SMM), email marketing, pay-per-click advertising (PPC), and influencer marketing on small business growth. Special attention is given to assessing the return on investment (ROI) using Google Analytics, Facebook Business Manager, and other analytical tools. The research finds that SEO and email marketing provide long-term sustainability, whereas PPC advertising and influencer marketing offer quick but more costly results. The article presents recommendations for selecting and optimizing the most effective marketing strategies for small businesses.